University Partnership Sebagai Akselerator Transformasi Digital Usaha Mikro Perempuan - Ghaling Achmad Abdul Ghonisyah; Irly Artiara Irawan (JMK (Jurnal Manajemen dan Kewirausahaan), 2023)
The partnership built by the university is one of the drivers of efforts to accelerate the digital transformation of women's micro-enterprises. The resources owned by the university can function as social capital to help micro-enterprises owned by women who experience gaps in access to opportunities for transformation, one of which will be the focus of this research is inequality in gaining entry to digital literacy. In this context, research on the role of university partnerships is compelling as an accelerator for inclusively advancing digital literacy for women micro-entrepreneurs in Indonesia, especially in the Tasikmalaya area. We used a qualitative approach conducting In-Depth Interviews with six informants who split up into 4 (four) clusters, specifically 1) University Cluster, 2) The Expert Cluster, 3) Micro-Entrepreneur Cluster, and 4) The Business Incubator Cluster. Our contribution shows that adopting an integrated learning initiative can accelerate the mastery and use of digital skills among female micro-entrepreneurs. This study contributes to understanding how the university partnership model is implemented according to the capacity and business model of women's microenterprises.